Convergence monitoring as a basis for numerical analysis of changes of rock-mass quality and Hoek-Brown failure criterion parameters due to longwall excavation - Małkowski, Piotr; Ostrowski, Łukasz (Archives of mining sciences = Archiwum górnictwa, 2019)
In the longwall exploitation system, the main gates are subject of the most intensive movements of the rock mass, where the proximity of the excavation front is a key factor. The paper presents the results of a research on the constants mb and s of Hoek-Brown failure criterion for the rocks surrounding the gallery: shale, sandy shale, coal and medium-grained sandstone, in relation to the distance to longwall face. The research comprised numerical modeling based on convergence monitoring records. The convergence measurements were carried out on three stations in a selected maingate in a coal mine from Upper Silesia Coal Basin near Jastrzębie-Zdrój, concurrently with changing distance to the longwall face. The measured were the width, the height and the heave of the floor of the gate. The measurements showed that the convergence at the longwall-maingate crossing was 1.5-3 times greater than in the locations much further from the longwall face. It was demonstrated that this effect was due to continuously changing properties of the rock-mass surrounding the gallery that can be expressed as decreasing empirical parameters mb i s of Hoek-Brown’s criterion. These parameters are decreasing exponentially together with the distance to the longwall face The consistency between the theoretical and factual curve varies between 70% to 98%. The change of each of the parameters can be described by general equation P = a· exp(–b·d), where a, b are constants, and d is the distance to the excavation face. The authors highlight that during the measurements period the horizontal stress was 1.45 to 1.61 times greater than the concurrent vertical stress. The so high horizontal stress causes heave of unsupported gallery floor which is commonly observed in the mines in Silesia.